Stropharia lignicola (Strophariaceae, Agaricales), a new species with acanthocytes in the hymenium from China - Tian, Enjing; Gao, Chonghua; Xie, Xiaomei; Zheng, Yuan (Phytotaxa, 2021)
A new mushroom species from Hunnan province in China, Stropharia lignicola, is described. S. lignicola is distinguished from other species of Stropharia by its greyish yellow pileus, white stipe with recurved yellowish squamules, presence of acanthocytes in the hymenium, and association with decaying fallen wood or stumps of a hardwood species, Tilia sp. The phylogenetic analyses were based on ITS and 28S. An illustrated description of S. lignicola is provided along with a key to the Stropharia species found in China.